Incidencia de depresión en pacientes con VIH en la unidad de medicina familiar No. 82 Zamora Michoacán - Rangel Torres, Aldo David (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
BACKGROUND: Patients living with HIV-AIDS are increasingly living longer. Its greater tendency to suffer from infectious and oncological complications is known, and there is a predisposition to suffer from mental illnesses such as anxiety and depression. OBJECTIVE: Determine the incidence of depression in patients with HIV in the Family Medicine unit No.82 Zamora Michoacán. MATERIAL AND METHODS: Observational, descriptive, prospective and crosssectional study in which the Beck depression questionnaire (DBI-II) was carried out in patients living with HIV-AIDS assigned to the UMF # 82 in Zamora, Michoacán. Proposed statistical test: Measures of central tendency and median mean dispersion and interquartile range will be obtained with the Kolmogorov-Smirnov test, frequencies and percentages. For association of Chi-square variables. RESULT: In relation to the incidence of depression in the studied population, an incidence of 100% was obtained. Based on the Beck Depression Inventory (BDI-II), the predominant degree of depression was the minimum degree with 48.9% of the patients, the accompanying symptoms that were most associated were self-criticism and sleep disturbances.

ANTECEDENTES: Los pacientes que viven con VIH-SIDA son cada vez más longevos. Se conoce su mayor tendencia a padecer complicaciones infecciosas y oncológicas y existe la predisposición a padecer de enfermedades mentales como la ansiedad y depresión. OBJETIVO: Determinar la incidencia de depresión en pacientes con VIH en la Unidad de Medicina Familiar No. 82 Zamora, Michoacán. MATERIAL Y METODOS: Estudio observacional, descriptivo, prospectivo y transversal en el cual se realizará el cuestionario de depresión de Beck (DBI-II) en los pacientes que viven con VIH-SIDA adscritos a la UMF # 82 en Zamora, Michoacán. PRUEBA ESTADÍSTICA PROPUESTA: Se obtendrán medidas de tendencia central y dispersión media, mediana y rango intercuartílico con la prueba de Kolmogorov-Smirnov, frecuencias y porcentajes para asociación de variables Chi-cuadrada. RESULTADO: En relación a la incidencia de depresión en la población estudiada, se obtuvo una incidencia del 100%. En base al Inventario de Depresión de Beck (BDI-II) el grado de depresión predominante fue el grado mínimo con el 48.9% de los pacientes, los síntomas acompañantes que más se asociaron fueron la autocrítica y las alteraciones del sueño.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19091; info:eu-repo/classification/cti/3; FCMB-E-2025-0124; VIH-SIDA; Incidencia; Salud mental